Penyusunan semula proses pendaftaran hakmilik - Omar, Abdul Jalil (2004)
The registration of title for the process of land alienation (Serah Balik Kurnia Semula) is an important activity in property development. However, this process involves a lengthy cycle time which in turn affects the flow of other activities. The arrangement of activities involved in the flow of the work process has been identified the causal problem. Hence, this study seeks to identify ways to overcome the delay in the title registration process. Therefore, the structure of this study is firstly, is to identify the cycle time of the process. Secondly, is to identify the level of work efficiency as well as the factors contributing to the problem. The third objective of the study is to propose an alternative process for the registration of title in land alienation (SBKS). Accordingly, this study adopts the business process reengineering approach as its methodology. In this approach, the whole process is devided into various different nodes in which the time cycle and work efficiency for each nodes are identified. The nodes with the longest time cycle as well as lowest level of work efficiency was identified as requiring process reengineering. Finally, the study indicates that the proposed alternative process resulted from the business process reengeneering is able to shorten land alienation (SBKS) title registration cycle time from five month to one month.